Writers’ awareness, lingustic realisations and readers’ responses to metadiscourse features in Malaysian business news - Hooi, Chee Mei (2020)
Metadiscourse features (textual and interpersonal metadiscourse) also known as pragmatic features are ways in which writers express their opinions and construct a text to make it reader-friendly. Researchers have analysed metadiscourse features in different areas which include intercultural studies, gender studies, and academic discourse. However, studies on metadiscourse in news settings are limited. To date, only a few researchers such as Kuppers and Ho-Dac (2010), Lambiase (2010) and Yuryevna (2012) have conducted studies on metadiscourse in news discourse. To increase the existing pool of literature on metadiscourse, this study sought to investigate the awareness of the use of metadiscourse features by writers of two online business news portals: The Star Online and Focus Malaysia. This study also aimed to identify the linguistic realisations and categories of metadiscourse categories that were commonly used in business news. Apart from that, responses of readers to the business news with metadiscourse and those without metadiscourse were examined. A mixed-method approach was employed and a modified Dafouz-Milne’s (2008) model was used as an analytical framework in this study. Metadiscourse Awareness Test and a collection of 50 business news items from The Star Online and Focus Malaysia were used as quantitative data collections. For the qualitative analysis, news with and without metadiscourse, as well as writing prompts were used in this study. Two types of sampling methods were adopted in the study. Purposive sampling was used to select 10 The Star Online writers and 10 Focus Malaysia writers to test their awareness of the use of metadiscourse in the writing of business news. Fifty business news were also selected purposively from the two news portals respectively to analyse the linguistic realisations of metadiscourse features. Moreover, 30 students from English major courses were chosen through convenience sampling to examine the readers’ responses to news with the presence and the absence of metadiscourse. The findings of this study showed that both The Star Online and Focus Malaysia writers had a bit of difficulty in identifying announcements and sequencers for textual metadiscourse, but not in other categories of interpersonal metadiscourse. Besides that, the findings revealed that the use of both textual and interpersonal metadiscourse was prevalent in both the news portals. Textual metadiscourse was used much more frequently than interpersonal metadiscourse in The Star Online, whereas in Focus Malaysia, both textual and interpersonal metadiscourse were used. The data also revealed that the frequency of metadiscourse used varied across the different categories. For readers’ response, it was found that most students preferred to read news with textual and interpersonal metadiscourse because they believed that through the use of metadiscourse, the news was more comprehensible and readerfriendly. To conclude, metadiscourse are useful writing devices that help produce engaging prose, academic or otherwise. It is important that the awareness of metadiscourse in business news among the writers be heightened through the use of Metadiscourse Awareness Test. The linguistic realisations of metadiscourse features could also be used as useful means for the writers to know the role of metadiscourse in business news discourse.